Question about Texas Instruments TI-89 Calculator

Ad

Type cFactor for this expression! See captured image!

Posted on Dec 08, 2011

Ad

Neither does my TI-89 Titanium. There is no simple factoring for this expression.

Posted on Aug 01, 2010

Ad

Hi,

a 6ya expert can help you resolve that issue over the phone in a minute or two.

Best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

the service is completely free and covers almost anything you can think of.(from cars to computers, handyman, and even drones)

click here to download the app (for users in the US for now) and get all the help you need.

Goodluck!

Posted on Jan 02, 2017

I assume the 10x2 means 10 squared. (I will show it as 10x**2)

(22x+11)(10x**2+5x) factors into"

11(2x+1)*5(2x**2+1x)

=55(2x+1)(2x**2+1x)

=(55x)(2x+1)(2x+1)

Multiplied out, it becomes 55x(4x**2+4x+1)

= 220x**3 + 220x**2 + 55x

(22x+11)(10x**2+5x) factors into"

11(2x+1)*5(2x**2+1x)

=55(2x+1)(2x**2+1x)

=(55x)(2x+1)(2x+1)

Multiplied out, it becomes 55x(4x**2+4x+1)

= 220x**3 + 220x**2 + 55x

Dec 11, 2014 | Computers & Internet

5[x(2+y)] What is the associative law to of addition to this expression?
Wrong forum category but...
The associative law of addition does just that: it associates some factor (some multiplier) in an expression with all of the terms in string of addends by which the factor will be multiplies. I na nutshell, the laws holds, for example, that in the expression, 5[x(2+y)], the factor, x, can be multiplied by each term of the sum (2+y), without first finding their total, to arrive at (2x + yx); and, in turn, those terms can be separately associated again with the factor, 5, in order to arrive at the equation,

5(2x + yx) = 10x + 5xy. Note also that the law includes its reverse, by which terms can be dissociated and summed prior to being multiplied by a former distributed factor.

5(2x + yx) = 10x + 5xy. Note also that the law includes its reverse, by which terms can be dissociated and summed prior to being multiplied by a former distributed factor.

Oct 31, 2014 | Computers & Internet

Factor out 3X

3X(2X-5)=0

The expression is equal to zero if one of the factors on the left side equals zero.

1st solution: 3X=0, thus X=0

2nd solution 2X-5 = 0 if X=5/2

3X(2X-5)=0

The expression is equal to zero if one of the factors on the left side equals zero.

1st solution: 3X=0, thus X=0

2nd solution 2X-5 = 0 if X=5/2

Sep 10, 2010 | Office Equipment & Supplies

There are several factoring programs available at

http://www.ticalc.org/pub/83plus/basic/math/algebra/

http://www.ticalc.org/pub/83plus/basic/math/algebra/

Aug 19, 2010 | Texas Instruments TI-84 Plus Silver...

You can solve it with following method.

5x+3y=6 2x-4y=5

So 5x=6-3y so 2[(6-3y)/5]-4y=5

So x=(6-3y)/5 so 12-6y-20y=25

so -26y=25-12

so -26y=13

so y= -(1/2)

2x-4y=5

so 2x=5+4y

so 2x=5+4(-1/2)

so 2x=(10-4)/2

so 2x=6/4

so x =3/2

The value of x=3/2 and value of y= -1/2

Let me know if you need further assistance.

Thanks for using FixYa.

5x+3y=6 2x-4y=5

So 5x=6-3y so 2[(6-3y)/5]-4y=5

So x=(6-3y)/5 so 12-6y-20y=25

so -26y=25-12

so -26y=13

so y= -(1/2)

2x-4y=5

so 2x=5+4y

so 2x=5+4(-1/2)

so 2x=(10-4)/2

so 2x=6/4

so x =3/2

The value of x=3/2 and value of y= -1/2

Let me know if you need further assistance.

Thanks for using FixYa.

Mar 03, 2010 | Office Equipment & Supplies

Hi,

There 4 or 5 programs for the TI83/4Plus family of calculators available at ticlac.org. Scroll down the page to find them. Download them and transfert to your calculator using TIConnectivity software.

Hope it helps.

Thank you for using fixYa and for rating the solution.

There 4 or 5 programs for the TI83/4Plus family of calculators available at ticlac.org. Scroll down the page to find them. Download them and transfert to your calculator using TIConnectivity software.

Hope it helps.

Thank you for using fixYa and for rating the solution.

Dec 02, 2009 | Texas Instruments TI-84 Plus Calculator

6x+6=4x+12

Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.

6x+6-4x=12

Since 6x and -4x are like terms, add -4x to 6x to get 2x.

2x+6=12

Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.

2x=-6+12

Add 12 to -6 to get 6.

2x=6

Divide each term in the equation by 2.

(2x)/(2)=(6)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=(6)/(2)

Simplify the right-hand side of the equation by simplifying each term.

x=3

Good Luck

Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.

6x+6-4x=12

Since 6x and -4x are like terms, add -4x to 6x to get 2x.

2x+6=12

Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.

2x=-6+12

Add 12 to -6 to get 6.

2x=6

Divide each term in the equation by 2.

(2x)/(2)=(6)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=(6)/(2)

Simplify the right-hand side of the equation by simplifying each term.

x=3

Good Luck

Sep 10, 2009 | Audio Players & Recorders

Unless I am failing to understand your problem, just combine like terms to get:

9x^2+2x+4 and then enter those coefficients into the quadratic solver.

That will get you the two answers -- both of them will be complex.

If you wanted to turn those two answers into factors (complex) of the original equation simply

change the signs on each and put an x in front.

Of course, the quadratic formula would also work.

CG

9x^2+2x+4 and then enter those coefficients into the quadratic solver.

That will get you the two answers -- both of them will be complex.

If you wanted to turn those two answers into factors (complex) of the original equation simply

change the signs on each and put an x in front.

Of course, the quadratic formula would also work.

CG

Apr 17, 2009 | Casio FX-115ES Scientific Calculator

Well, to answer part of your question, yes... the TI-89 does factor like this. it is inputted like this:

factor(6*x^2+11*x+4,x)

Check the catalog in the TI-84 (which is 2nd-zero) and look under F for factor()

factor(6*x^2+11*x+4,x)

Check the catalog in the TI-84 (which is 2nd-zero) and look under F for factor()

Jan 12, 2009 | Texas Instruments TI-89 Calculator

WHAT IS THE KEY OR KEYS TO GET THE INVERSE LOG FUNCTION?

Apr 02, 2008 | Texas Instruments TI-89 Calculator

May 21, 2014 | Texas Instruments TI-89 Calculator

Feb 17, 2014 | Texas Instruments TI-89 Calculator

167 people viewed this question

Usually answered in minutes!

×